Organisational interventions to reduce length of stay in hospital: a rapid evidence assessment - Céline Miani; Sarah Ball; Emma Pitchforth; Josephine Exley; Sarah King; Martin Roland; Jonathan Fuld; Ellen Nolte (National Institute for Health Research, 2014)
Background: Available evidence on effective interventions to reduce length of stay in hospital is wide-ranging and complex, with underlying factors including those acting at the health system, organisational and patient levels, and the interface between these. There is a need to better understand the diverse literature on reducing the length of hospital stay. Objectives: This study sought to (i) describe the nature of interventions that have been used to reduce length of stay in acute care hospitals; (ii) identify the factors that are known to influence length of stay; and (iii) assess the impact of interventions on patient outcomes, service outcomes and costs. Data sources: We searched MEDLINE (Ovid), EMBASE, the Health Management Information Consortium and System for Information on Grey Literature in Europe for the period January 1995 to January 2013 with no limitation of publication type. Methods: We conducted a rapid evidence synthesis of the peer-reviewed literature on organisational interventions set in or initiated from acute hospitals. We considered evidence published between 2003 and 2013. Data were analysed drawing on the principles of narrative synthesis. We also carried out interviews with eight NHS managers and clinical leads in four sites in England. Results: A total of 53 studies met our inclusion criteria, including 19 systematic reviews and 34 primary studies. Although the overall evidence base was varied and frequently lacked a robust study design, we identified a range of interventions that showed potential to reduce length of stay. These were multidisciplinary team working, for example some forms of organised stroke care; improved discharge planning; early supported discharge programmes; and care pathways. Nursing-led inpatient units were associated with improved outcomes but, if anything, increased length of stay. Factors influencing the impact of interventions on length of stay included contextual factors and the population targeted. The evidence was mixed with regard to the extent to which interventions seeking to reduce length of stay were associated with cost savings. Limitations: We only considered assessments of interventions which provided a quantitative estimate of the impact of the given organisational intervention on length of hospital stay. There was a general lack of robust evidence and poor reporting, weakening the conclusions that can be drawn from the review. Conclusions: The design and implementation of an intervention seeking to reduce (directly or indirectly) the length of stay in hospital should be informed by local context and needs. This involves understanding how the intervention is seeking to change processes and behaviours that are anticipated, based on the available evidence, to achieve desired outcomes ('theory of change'). It will also involve assessing the organisational structures and processes that will need to be put in place to ensure that staff who are expected to deliver the intervention are appropriately prepared and supported. With regard to future research, greater attention should be given to the theoretical underpinning of the design, implementation and evaluation of interventions or programmes. There is a need for further research using appropriate methodology to assess the effectiveness of different types of interventions in different settings. Different evaluation approaches may be useful, and closer relationships between researchers and NHS organisations would enable more formative evaluation. Full economic costing should be undertaken where possible, including considering the cost implications for the wider local health economy. Funding: The National Institute for Health Research Health Services and Delivery Research programme.